Infraethics and social bonding - Terravecchia, Gian Paolo (Scenari, 2021)
In recent times, on one side, social philosophy is showings the importance of social obligations not reducible to moral duties and yet important for the field of morality. On the other side, information ethics is stressing the importance of infraethics, as ethical infrastructure. One may think that these two fields, social philosophy and information ethics, have very little in common, but at a closer look that is not the case. This is because, as the paper tries to show, social bonds are an important infraethics element. The paper starts introducing the notion of infraethics and, after this, some basic elements of the philosophy of social bonds. On this ground, the Cambridge Analytica case is discussed to clarify which was the most serious violation committed.